Externally modulated theranostic nanoparticles - Urban, Cordula; Urban, Alexander S.; Charron, Heather; Joshi, Amit (Translational Cancer Research; Vol 2, No 4 (August 26, 2013): Translational Cancer Research (Nanotechnology in Radiation Research), 2013)
Externally modulated nanoparticles comprise a rapidly advancing class of cancer nanotherapeutics, which combine the favorable tumor accumulation of nanoparticles, with external spatio-temporal control on therapy delivery via optical, magnetic, or ultrasound modalities. The local control on therapy enables higher tumor treatment efficacy, while simultaneously reducing off-target effects. The nanoparticle interactions with external fields have an additional advantage of frequently generating an imaging signal, and thus such agents provide theranostic (both diagnostic and therapeutic) capabilities. In this review, we classify the emerging externally modulated theranostic nanoparticles according to the mode of external control and describe the physiochemical mechanisms underlying the external control of therapy, and illustrate the major embodiments of nanoparticles in each class with proven biological efficacy: (I) electromagnetic radiation in visible and nearinfrared range is being exploited for gold based and carbon nanostructures with tunable surface plasmon resonance (SPR) for imaging and photothermal therapy (PTT) of cancer, photochemistry based manipulations are employed for light sensitive liposomes and porphyrin based nanoparticles; (II) Magnetic field based manipulations are being developed for iron-oxide based nanostructures for magnetic resonance imaging (MRI) and magnetothermal therapy; (III) ultrasound based methods are primarily being employed to increase delivery of conventional drugs and nanotherapeutics to tumor sites.